Bunker auscultation: A classification system for a proto-method of sensory space composition. (10th October 2011) - EMMETT, MATHEW
A subterranean WWII bunker, hidden under the City of Plymouth, is used as the context for the investigation. The enquiry considers the bunker as psychoactive in nature, that is, stimulating a range of psychological, emotional and behavioural responses in relationship to the percipient's spatial register. The project focuses on developing a classification system, and examines space as a conveying medium. The project acts as a scheme for establishing a critical methodology of sensory space and develops an interdisciplinary architectural language for thinking about architecture as phenomenological constructions, whilst implying a greater understanding of the roles of mnemonic structures.